Silicon-based composite negative electrode material and preparation method thereof, lithium battery negative electrode material and lithium battery
By using a silicon-based composite anode material with a general structure of LixMgySizOw in lithium-ion batteries, combined with prelithiation treatment and carbon cladding, the problems of high irreversible capacity of the silicon-based anode material in the first week and low Coulomb efficiency for the first time are solved. More efficient electrochemical performance and lower cost are achieved.
Patent Information
- Application Number
- CN202011148659.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-10-23
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2040-10-23
AI Technical Summary
The existing silicon-based anode materials have problems such as high irreversible capacity in the first week and low Coulomb efficiency in lithium-ion batteries.
Using silicon-based composite anode material with structural general formula LixMgySizOw, the material optimizes the molar ratio of silicon to oxygen and doping of magnesium by combining prelithiation and carbon cladding to reduce unstable SEI films and irreversible silicon. The formation of acid salts.
The first Coulomb efficiency of silicon-based anode material is significantly improved, irreversible capacity loss is reduced, and the cost of the material is reduced.
Smart Images

Figure CN112382753B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a silicon-based composite negative electrode material and a preparation method thereof, a lithium battery negative electrode material and a lithium battery. Background Art
[0002] The specific capacity of traditional graphite anode is only 372mAh / g, while the theoretical specific capacity of silicon can reach 4200mAh / g. At the same time, silicon has a low lithium insertion and extraction voltage platform (compared with Li / Li + Compared with lithium ions, silicon has many advantages, such as low voltage (less than 0.5V), low electrolyte reactivity, abundant reserves, mature silicon purification process and low price. Therefore, silicon has great potential as anode material for lithium-ion batteries. Silicon is even considered to be an ideal cathode material for the next generation of high energy density lithium-ion batteries. However, when silicon is used as an anode material, the electrochemical performance of lithium-ion batteries is easily deteriorated during the process of lithium ion insertion and extraction due to the huge volume effect of silicon-based anode materials and unstable surface solid electrolyte interface film (SEI film), which in turn limits its commercial application.
[0003] At present, with the study of silicon and silicon-based materials, researchers have found that SiO x Due to its strong silicon-oxygen bond and the buffering effect of lithium silicate and Li2O formed during the cycle on volume expansion, it has excellent cycle performance and is one of the important directions for the development of silicon-based negative electrode materials. However, the irreversible formation of lithium silicate and Li2O and the unstable SEI film generated during the cycle still lead to the degradation of SiO x The irreversible capacity in the first week is high, and the first coulombic efficiency is less than 80%, which is far lower than the 90% required for actual industrial applications. Summary of the invention
[0004] The main purpose of the present invention is to provide a silicon-based composite negative electrode material and a preparation method thereof, a lithium battery negative electrode material and a lithium battery, so as to solve the problems of high first-cycle irreversible capacity and low first coulombic efficiency of silicon-based negative electrode materials in the prior art.
[0005] In order to achieve the above object, according to one aspect of the present invention, a silicon-based composite negative electrode material is provided. The silicon-based composite negative electrode material has a general structural formula Li x Mg y Si z O w , where 0.10≤x≤0.20, 2.00≤y≤2.20, z=6.8, 5.30≤w≤7.10.
[0006] Furthermore, the silicon-based composite negative electrode material further comprises a carbon coating layer, the carbon coating layer covers the Li x Mg y Siz O w On the outer surface of the carbon coating layer, the thickness of the carbon coating layer is preferably 10 to 500 nm.
[0007] Furthermore, the above Li x Mg y Si z O w The D50 is 1-6 μm, preferably Li x Mg y Si z O w The ratio of D50 to the thickness of the carbon coating layer is 200-500:1.
[0008] According to another aspect of the present invention, a method for preparing the aforementioned silicon-based composite negative electrode material is provided, the preparation method comprising: pre-lithiation treatment of silicon, silicon dioxide and lithium magnesium silicate to obtain Li x Mg y Si z O w , the pre-lithiation treatment is carried out in vacuum.
[0009] Furthermore, the preparation method comprises: pressing and molding the raw materials including silicon, silicon dioxide and lithium magnesium silicate to obtain a molded product; performing a pre-lithiation treatment on the molded product to obtain Li x Mg y Si z O w Preferably, the shape of the product after molding is selected from any one of a sphere, a tetrahedron, and a cuboid.
[0010] Furthermore, the temperature of the pre-lithiation treatment is 1400-1700°C. Preferably, the pre-lithiation treatment is heated to 1400-1700°C at a heating rate of 5-10°C / min. Preferably, the pre-lithiation treatment is performed for 5-15h after the heating is completed.
[0011] Furthermore, the particle size of the silicon is 5 to 100 nm, and the particle size of the silicon dioxide is preferably 5 to 20 μm.
[0012] Furthermore, the preparation method further comprises: x Mg y Si z O wThe crushed material is crushed to obtain a crushed material; the crushed material is coated with a carbon source to obtain a silicon-based composite negative electrode material, wherein the particle size of the crushed material is preferably 0.5-5 μm, and the coating process preferably includes: heating the crushed material to 500-600° C. and then introducing a carbon source for cracking, wherein the cracking time is preferably 0.5-5 h, and the heating rate is preferably 5-10° C. / min. The carbon source is preferably selected from any one or more of methane, acetylene, propyne, and propylene, and the flow rate of the carbon source is preferably 0.1-1 L / min.
[0013] According to another aspect of the present invention, a lithium battery negative electrode material is provided. The lithium battery negative electrode material includes a silicon-based negative electrode material, and the silicon-based negative electrode material is the aforementioned silicon-based composite negative electrode material.
[0014] According to another aspect of the present invention, a lithium battery is provided, comprising a negative electrode and a positive electrode, wherein the negative electrode is the aforementioned negative electrode material for the lithium battery.
[0015] Applying the technical solution of the present invention, the general structural formula of the present application is Li x Mg y Si z O w In the figure, even without considering Li and Mg, the molar ratio of oxygen to silicon is less than 2:1, indicating that the silicon therein is not present in the form of silicon dioxide. On the one hand, the silicon-based composite negative electrode material can compensate for the loss of active lithium in the battery during the cycle, thereby reducing the unstable SEI, irreversible silicates and Li2O generated by the silicon-based negative electrode material during the cycle, thereby improving the first coulombic efficiency of the silicon-based negative electrode material. On the other hand, the above-mentioned silicon-based composite negative electrode material can achieve magnesium doping, so that magnesium and lithium form an alloy to reduce the formation of irreversible lithium silicates and Li2O, further reducing the irreversible capacity loss of the silicon-based negative electrode material and improving its first coulombic efficiency, and the material composition is simple and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0017] Figure 1 A 1000-cycle retention rate graph of the silicon-based negative electrode materials provided in Examples 1 to 3, Examples 29, 30 and Comparative Example 1 of the present application is shown. DETAILED DESCRIPTION
[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0019] As analyzed in the background technology, the prior art has the problem that the first-cycle irreversible capacity of silicon-based negative electrode materials is high and the first coulombic efficiency is low. To solve this technical problem, the present invention provides a silicon-based composite negative electrode material and a preparation method thereof, a lithium battery negative electrode material and a lithium battery.
[0020] In a typical embodiment of the present application, a silicon-based composite negative electrode material is provided, wherein the silicon-based composite negative electrode material has a structural formula Li x Mg y Si z O w , where 0.10≤x≤0.20, 2.00≤y≤2.20, z=6.8, 5.30≤w≤7.10.
[0021] The general structural formula of this application is Li x Mg y Si z O w In the figure, even without considering Li and Mg, the molar ratio of oxygen to silicon is less than 2:1, indicating that the silicon therein is not present in the form of silicon dioxide. On the one hand, the silicon-based composite negative electrode material can compensate for the loss of active lithium in the battery during the cycle, thereby reducing the unstable SEI, irreversible silicates and Li2O generated by the silicon-based negative electrode material during the cycle, thereby improving the first coulombic efficiency of the silicon-based negative electrode material. On the other hand, the above-mentioned silicon-based composite negative electrode material can achieve magnesium doping, so that magnesium and lithium form an alloy to reduce the formation of irreversible lithium silicates and Li2O, further reducing the irreversible capacity loss of the silicon-based negative electrode material and improving its first coulombic efficiency, and the material composition is simple and the cost is low.
[0022] In order to further reduce the direct contact probability between the silicon-based composite negative electrode material and the electrolyte solution, thereby reducing the loss of the silicon-based composite negative electrode material and at the same time buffering the volume effect of the silicon-based negative electrode material, the silicon-based composite negative electrode material preferably further includes a carbon coating layer, the carbon coating layer covers the Li x Mg y Si z O w On the outer surface of the silicon-based composite negative electrode material, the thickness of the carbon coating layer is preferably 10 to 500 nm. Such a thickness further enhances the strength of the carbon coating layer and improves the performance of the silicon-based composite negative electrode material.
[0023] In one embodiment of the present application, the above-mentioned Li x Mg y Si z O w The D50 is 1-6 μm, preferably Li x Mg y Si z O wThe ratio of D50 to the thickness of the carbon coating layer is 200-500:1.
[0024] Control Li x Mg y Si z O w When the thickness of the carbon coating layer is within the above range, it is beneficial to minimize the thickness of the carbon coating layer and its proportion in the entire battery while protecting the direct contact between the silicon-based composite negative electrode material and the electrolyte solution and mitigating the volume effect, thereby obtaining a silicon-based negative electrode material as light as possible.
[0025] In another typical embodiment of the present application, a method for preparing the aforementioned silicon-based composite negative electrode material is provided, the preparation method comprising: pre-lithiation treatment of silicon, silicon dioxide and lithium magnesium silicate to obtain Li x Mg y Si z O w , the pre-lithiation treatment is carried out in vacuum.
[0026] Silicon, silicon dioxide and lithium magnesium silicate are pre-lithiated to obtain a product having the general structural formula Li x Mg y Si z O w The silicon-based composite negative electrode material can be pre-lithiated in a vacuum to prevent silicon from being oxidized to silicon dioxide, thereby ensuring the formation of the above-mentioned silicon-based composite negative electrode material and improving the efficiency of the pre-lithiation treatment. And the silicon-based composite negative electrode material formed by this method can, on the one hand, compensate for the loss of active lithium in the battery during the cycle process, thereby reducing the unstable SEI, irreversible silicates and Li2O generated by the silicon-based negative electrode material during the cycle process, thereby improving the first coulomb efficiency of the silicon-based negative electrode material. On the other hand, the above-mentioned silicon-based composite negative electrode material can achieve magnesium doping, so that magnesium and lithium form an alloy to reduce the formation of irreversible lithium silicates and Li2O, thereby reducing the irreversible capacity loss of the silicon-based negative electrode material and improving its first coulomb efficiency, and the material composition is simple and the cost is low.
[0027] The preparation method of lithium magnesium silicate can refer to the prior art, for example, it can be prepared by the following method:
[0028] According to the molar ratio of silicon dioxide (5 μm), lithium fluoride (5 μm) and magnesium chloride (5 μm) of 8: (1-2): (5-5.5), a water suspension with a solid content of 5-25% is prepared. After the water suspension is stirred at a speed of 1000 r / min and heated to 200°C, the stirring speed is continued to be 1000 r / min, and 1M ammonia water is added dropwise at a speed of 1.5 L / min until the pH is 10.0, and the stirring is continued and the temperature is kept for 3 hours to obtain lithium magnesium silicate. The lithium magnesium silicate used in the following examples is all this lithium magnesium silicate.
[0029] In one embodiment of the present application, the preparation method comprises: pressing and molding raw materials including silicon, silicon dioxide and lithium magnesium silicate to obtain a molded product; performing a pre-lithiation treatment on the molded product to obtain Li x Mg y Si z O w .
[0030] By pressing and molding the raw materials including silicon, silicon dioxide and lithium magnesium silicate, the powders of silicon, silicon dioxide and lithium magnesium silicate can be densified, which is convenient for the rapid migration of atoms in the subsequent alloying process, thereby quickly forming a uniform silicon-based composite negative electrode material. According to the pressing and molding instrument and the actual operation requirements, the shape of the molded product is preferably selected from any one of a sphere, a tetrahedron and a cuboid.
[0031] In order to improve the efficiency of the pre-lithiation treatment, the temperature of the pre-lithiation treatment is preferably 1400-1700°C, and the pre-lithiation treatment process is preferably heated to 1400-1700°C at a heating rate of 5-10°C / min, and the pre-lithiation treatment time after the heating is preferably 5-15 hours. Preferably, the above heating rate and pre-lithiation treatment time can take into account the uniformity of the formed silicon-based composite negative electrode material and the efficiency of the pre-lithiation treatment.
[0032] In order to mix silicon, silicon dioxide and lithium magnesium silicate more fully, thereby obtaining a silicon-based composite negative electrode material in which each component is evenly dispersed, and thereby ensuring that the silicon-based composite negative electrode material has excellent performance, the particle size of the above silicon is preferably 5 to 100 nm, and the particle size of the silicon dioxide is preferably 5 to 20 μm.
[0033] In one embodiment of the present application, the preparation method further comprises: x Mg y Si z O wThe crushed material is crushed to obtain a crushed material; the crushed material is coated with a carbon source to obtain a silicon-based composite negative electrode material, and the coating process preferably includes: heating the crushed material to 500-600°C and then introducing a carbon source for cracking, the cracking time is preferably 0.5-5h, the heating rate is preferably 5-10°C / min, the carbon source is preferably selected from any one or more of methane, acetylene, propyne, and propylene, and the flow rate of the carbon source is preferably 0.1-1L / min.
[0034] Broken Li x Mg y Si z O w It has a smaller volume, so that the carbon source can cover it more fully. To further improve the coating effect, the particle size of the crushed material is preferably 0.5-5 μm. The carbon source is introduced and cracked at 500-600 ° C, so that the carbon source covers the crushed material in the form of gas phase, which is beneficial to improve the fluidity of the gas molecular carbon source. The gas molecular carbon source has a smaller volume, so it can enter the Li more quickly. x Mg y Si z O w The deep voids and defects of the silicon-based composite anode material are formed with targeted carbon coating. The flow rate of the carbon source, the cracking time and the heating rate work together to achieve better carbon coating effect under more favorable conditions, thereby obtaining a silicon-based composite anode material with excellent performance.
[0035] In another typical embodiment of the present application, a lithium battery negative electrode material is provided. The lithium battery negative electrode material includes a silicon-based negative electrode material, and the silicon-based negative electrode material is the aforementioned silicon-based composite negative electrode material.
[0036] The above-mentioned silicon-based composite negative electrode material has the characteristic of low irreversible capacity in the first cycle, so using it as a negative electrode material for lithium batteries can effectively improve the performance of lithium-ion batteries such as the first coulombic efficiency.
[0037] In another typical embodiment of the present application, a lithium battery is provided, comprising a negative electrode and a positive electrode, wherein the negative electrode is the aforementioned negative electrode material of the lithium battery.
[0038] The aforementioned negative electrode material for lithium batteries has excellent performance, and therefore, using the negative electrode material for lithium batteries as the negative electrode of lithium batteries can effectively improve the corresponding electrical performance of lithium batteries.
[0039] The beneficial effects of the present application will be described below in conjunction with specific embodiments and comparative examples.
[0040] According to the molar ratio of silicon dioxide (5 μm), lithium fluoride (5 μm) and magnesium chloride (5 μm) of 8:2:5, a water suspension with a solid content of 20% was prepared. After the water suspension was stirred at a speed of 1000 r / min and heated to 200°C, the stirring speed was continued to be 1000 r / min, and 1M ammonia water was added dropwise at a speed of 1.5 L / min until the pH = 10.0, and the stirring was continued and the temperature was kept for 3 hours to obtain lithium magnesium silicate. The lithium magnesium silicate used in the following examples is all this lithium magnesium silicate.
[0041] Example 1
[0042] Silicon (particle size of 5 nm), silicon dioxide (particle size of 5 μm) and lithium magnesium silicate were mixed in a molar ratio of 9:9:1 and dried to obtain a dry mixture, which was then sent to a powder press and pressed in nitrogen to form a spherical product with a diameter of 0.5 μm. The formed product was sent to a vacuum furnace (with a pressure of 100 Pa) and heated to form a gas. The temperature was raised to 1600°C at a heating rate of 10°C / min and then kept at this temperature for 10 hours. The gas was condensed in the condensation chamber of the vacuum furnace to form Li x Mg y Si z O w .
[0043] Li x Mg y Si z O w The crushed materials were sent to a pulverizer and crushed into materials with a size of less than 5 μm (D50). The crushed materials were sent to a rotary kiln and heated to 600°C at a heating rate of 10°C / min. Methane (flow rate of 0.1 L / min) was then introduced into the rotary kiln for cracking for 5 hours. The silicon-based composite negative electrode material was finally obtained.
[0044] Example 2
[0045] The difference between Example 2 and Example 1 is that:
[0046] The heating rate of the pre-lithiation treatment is 5°C / min, and the final silicon-based composite negative electrode material is obtained.
[0047] Example 3
[0048] The difference between Example 3 and Example 1 is that:
[0049] The heating rate of the pre-lithiation treatment is 15°C / min, and the final silicon-based composite negative electrode material is obtained.
[0050] Example 4
[0051] The difference between Example 4 and Example 1 is that,
[0052] The temperature of the pre-lithiation treatment is 1400°C, and the final silicon-based composite negative electrode material is obtained.
[0053] Example 5
[0054] The difference between Example 5 and Example 1 is that
[0055] The temperature of the pre-lithiation treatment is 1700°C, and the final silicon-based composite negative electrode material is obtained.
[0056] Example 6
[0057] The difference between Example 6 and Example 1 is that
[0058] The temperature of the pre-lithiation treatment is 1300°C, and the final silicon-based composite negative electrode material is C@Li x Mg y Si z O w .
[0059] Example 7
[0060] The difference between Example 7 and Example 1 is that
[0061] The pre-lithiation treatment time is 15h, and the final silicon-based composite negative electrode material is obtained.
[0062] Example 8
[0063] The difference between Example 8 and Example 1 is that,
[0064] The pre-lithiation treatment time is 5 hours, and the final silicon-based composite negative electrode material is obtained.
[0065] Example 9
[0066] The difference between Example 9 and Example 1 is that
[0067] The pre-lithiation treatment time is 3h, and the final silicon-based composite negative electrode material is obtained.
[0068] Example 10
[0069] The difference between Example 10 and Example 1 is that
[0070] The particle size of silicon is 50 nm, and the final silicon-based composite negative electrode material is obtained.
[0071] Embodiment 11
[0072] The difference between Example 11 and Example 1 is that
[0073] The particle size of silicon is 100 nm, and the final silicon-based composite negative electrode material is obtained.
[0074] Example 12
[0075] The difference between Example 12 and Example 1 is that
[0076] The particle size of silicon is 120nm, and the final silicon-based composite negative electrode material is obtained.
[0077] Example 13
[0078] The difference between Example 13 and Example 1 is that
[0079] The particle size of silicon dioxide is 15 μm, and the final silicon-based composite negative electrode material is obtained.
[0080] Embodiment 14
[0081] The difference between Example 14 and Example 1 is that
[0082] The particle size of silicon dioxide is 20 μm, and the final silicon-based composite negative electrode material is obtained.
[0083] Embodiment 15
[0084] The difference between Example 15 and Example 1 is that
[0085] The particle size of silicon dioxide is 3 μm, and the final silicon-based composite negative electrode material is obtained.
[0086] Example 16
[0087] The difference between Example 16 and Example 1 is that
[0088] The D50 of the crushed material is 0.5 μm, and the final silicon-based composite negative electrode material is obtained.
[0089] Embodiment 17
[0090] The difference between Example 17 and Example 1 is that
[0091] The D50 of the crushed material is 3 μm, and the final silicon-based composite negative electrode material is obtained.
[0092] Embodiment 18
[0093] The difference between Example 18 and Example 1 is that
[0094] The D50 of the crushed material is 7 μm, and the final silicon-based composite negative electrode material is obtained.
[0095] Embodiment 19
[0096] The difference between Example 19 and Example 1 is that
[0097] The temperature for carbon source cracking is 500°C, and a silicon-based composite negative electrode material is finally obtained.
[0098] Embodiment 20
[0099] The difference between Example 20 and Example 1 is that
[0100] The temperature for carbon source cracking is 550°C, and the final silicon-based composite negative electrode material is obtained.
[0101] Embodiment 21
[0102] The difference between Example 21 and Example 1 is that
[0103] The temperature of carbon source cracking is 450°C, and the final silicon-based composite negative electrode material is obtained.
[0104] Embodiment 22
[0105] The difference between Example 22 and Example 1 is that
[0106] The heating rate during carbon source cracking is 5°C / min, and a silicon-based composite negative electrode material is finally obtained.
[0107] Embodiment 23
[0108] The difference between Example 23 and Example 1 is that
[0109] The heating rate during carbon source cracking is 7°C / min, and a silicon-based composite negative electrode material is finally obtained.
[0110] Embodiment 24
[0111] The difference between Example 24 and Example 1 is that
[0112] The heating rate during carbon source cracking is 20°C / min, and a silicon-based composite negative electrode material is finally obtained.
[0113] Embodiment 25
[0114] The difference between Example 25 and Example 1 is that
[0115] The flow rate of methane was 1 L / min, the cracking time was 3 h, and the final silicon-based composite negative electrode material was obtained.
[0116] Embodiment 26
[0117] The difference between Example 26 and Example 1 is that
[0118] The flow rate of methane was 0.1 L / min, the cracking time was 0.5 h, and the final silicon-based composite negative electrode material was obtained.
[0119] Embodiment 27
[0120] The difference between Example 27 and Example 1 is that
[0121] The flow rate of methane was 1.2 L / min, the cracking time was 5 h, and the final silicon-based composite negative electrode material was obtained.
[0122] Embodiment 28
[0123] The difference between Example 28 and Example 1 is that
[0124] The carbon source is propyne, and a silicon-based composite negative electrode material is finally obtained.
[0125] Embodiment 29
[0126] The difference between Example 29 and Example 1 is that
[0127] The dry mixture is not pressed and formed, but directly pre-lithiated to finally obtain a silicon-based composite negative electrode material.
[0128] Embodiment 30
[0129] The difference between Example 30 and Example 1 is that
[0130] Not right x Mg y Si z O w Carbon coating is performed to finally obtain a silicon-based composite negative electrode material.
[0131] Embodiment 31
[0132] The difference between Example 31 and Example 1 is that
[0133] Silicon (particle size of 5 nm), silicon dioxide (particle size of 5 μm) and lithium magnesium silicate are mixed in a molar ratio of 8:1:5.2 and dried to obtain a dry mixture, thereby finally obtaining a silicon-based composite negative electrode material.
[0134] Embodiment 32
[0135] The difference between Example 32 and Example 1 is that
[0136] Silicon (particle size of 5 nm), silicon dioxide (particle size of 5 μm) and lithium magnesium silicate are mixed in a molar ratio of 8:1.5:5.5 and dried to obtain a dry mixture, thereby finally obtaining a silicon-based composite negative electrode material.
[0137] Comparative Example 1
[0138] The difference between Comparative Example 1 and Example 1 is that
[0139] Without adding lithium magnesium silicate, only silicon and silicon dioxide are prepared into silicon-based negative electrode materials.
[0140] The SEM images of the cross-sections of the silicon-based composite negative electrode materials of Examples 1 to 32 and the silicon-based negative electrode material of Comparative Example 1 were used to obtain the thickness of their respective carbon coating layers. The D50 of the silicon-based composite negative electrode materials of Examples 1 to 32 and the silicon-based negative electrode material of Comparative Example 1 was tested using a laser particle size tester, and the test results are listed in Table 1.
[0141] The electrochemical performance tests of the silicon-based composite negative electrode materials of Examples 1 to 32 and the silicon-based negative electrode material of Comparative Example 1 were performed respectively according to the following test methods:
[0142] Take a silicon-based negative electrode material, and prepare it into a slurry according to the mass ratio of silicon-based negative electrode material, conductive graphite, sodium carboxymethyl cellulose, and styrene-butadiene rubber at 90:5:2.5:2.5 and stir it evenly. The slurry is evenly coated on a copper foil, and after vacuum drying for 24 hours, it is rolled to obtain a working electrode. The working electrode, lithium sheet counter electrode, polypropylene diaphragm, and 1M LiPF6 electrolyte are assembled into a button cell for electrochemical testing, and the test results are listed in Table 2, among which the 1000-week cycle retention rate of the silicon-based negative electrode materials of Examples 1 to 3, Example 29, Example 30, and Comparative Example 1 is as follows: Figure 1 shown.
[0143] Table 1
[0144]
[0145]
[0146] Table 2
[0147]
[0148]
[0149] As shown in Table 2, the irreversible capacity of the lithium battery prepared by the silicon-based composite negative electrode material prepared in Examples 1 to 32 of the present invention is significantly lower than that of the lithium battery prepared by the silicon-based negative electrode material in Comparative Example 1, and the coulombic efficiency is significantly higher than that of the lithium battery prepared by the silicon-based negative electrode material in Comparative Example 1. The coulombic efficiency of the batteries in Examples 1 to 32 is greater than 85%. Figure 1 It can be seen that after 1000 cycles, the battery capacity retention rates of Examples 1 to 32 are all greater than 85%, which is significantly higher than 75% of Comparative Example 1.
[0150] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0151] The general structural formula of this application is Li x Mg y Si z O wIn the figure, even without considering Li and Mg, the molar ratio of oxygen to silicon is less than 2:1, indicating that the silicon is not present in the form of silicon dioxide. On the one hand, the silicon-based composite negative electrode material can compensate for the loss of active lithium in the battery during the cycle, thereby reducing the unstable SEI, irreversible silicates and Li2O generated by the silicon-based negative electrode material during the cycle, thereby improving the first coulombic efficiency of the silicon-based negative electrode material. On the other hand, the above-mentioned silicon-based composite negative electrode material can achieve magnesium doping, so that magnesium and lithium form an alloy to reduce the formation of irreversible lithium silicates and Li2O, further reducing the irreversible capacity loss of the silicon-based negative electrode material and improving its first coulombic efficiency. In addition, the material has a simple composition and low cost.
[0152] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A silicon-based composite negative electrode material, characterized in that: The silicon-based composite negative electrode material has a structural formula of Li x Mg y Si z O w , where 0.10≤x≤0.20, 2.00≤y≤2.20, z=6.8, 5.30≤w≤7.10; Among them, the Li x Mg y Si z O w The preparation method comprises: Silicon, silicon dioxide and lithium magnesium silicate are pre-lithiated to obtain the Li x Mg y Si z O w ; The preparation method of the lithium magnesium silicate comprises: Raw materials including silicon dioxide, lithium fluoride and magnesium chloride are prepared into a water suspension, which is then heated and stirred under alkaline conditions to obtain the lithium magnesium silicate.
2. The silicon-based composite negative electrode material according to claim 1, characterized in that: The silicon-based composite negative electrode material further includes a carbon coating layer, the carbon coating layer covering the Li x Mg y Si z O w on the outer surface.
3. The silicon-based composite negative electrode material according to claim 2, characterized in that: The thickness of the carbon coating layer is 10 to 500 nm.
4. The silicon-based composite negative electrode material according to claim 2, characterized in that: The Li x Mg y Si z O w The D50 is 1~6μm.
5. The silicon-based composite negative electrode material according to claim 2, characterized in that: The Li x Mg y Si z O w The ratio of D50 to the thickness of the carbon coating layer is 200 to 500:
1.
6. The method for preparing the silicon-based composite negative electrode material according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Silicon, silicon dioxide and lithium magnesium silicate are pre-lithiated to obtain the Li x Mg y Si z O w , the pre-lithiation treatment is carried out in vacuum.
7. The preparation method according to claim 6, characterized in that: The preparation method comprises: Pressing and molding the raw materials including the silicon, the silicon dioxide and the lithium magnesium silicate to obtain a molded product; The formed product is subjected to the pre-lithiation treatment to obtain the Li x Mg y Si z O w .
8. The preparation method according to claim 7, characterized in that: The shape of the product after molding is selected from any one of a sphere, a tetrahedron, and a cuboid.
9. The preparation method according to claim 7, characterized in that: The temperature of the pre-lithiation treatment is 1400-1700°C.
10. The preparation method according to claim 7 or 9, characterized in that: The pre-lithiation treatment process is to heat the temperature to 1400-1700° C. at a heating rate of 5-10° C. / min.
11. The preparation method according to claim 10, characterized in that: The pre-lithiation treatment is performed for 5 to 15 hours after the temperature is raised.
12. The preparation method according to claim 7, characterized in that: The particle size of the silicon is 5 to 100 nm.
13. The preparation method according to claim 7, characterized in that: The particle size of the silicon dioxide is 5 to 20 μm.
14. The preparation method according to claim 7, characterized in that: The preparation method further comprises: The Li x Mg y Si z O w Crushing to obtain crushed materials; The crushed material is coated with a carbon source to obtain the silicon-based composite negative electrode material.
15. The preparation method according to claim 14, characterized in that: The particle size of the crushed material is 0.5 to 5 μm.
16. The preparation method according to claim 14, characterized in that: The coating treatment process includes: heating the crushed material to 500-600° C. and then introducing the carbon source to perform cracking.
17. The preparation method according to claim 16, characterized in that: The lysis time is 0.5 to 5 hours.
18. The preparation method according to claim 16, characterized in that: The heating rate is 5-10°C / min.
19. The preparation method according to claim 16, characterized in that: The carbon source is selected from any one or more of methane, acetylene, propyne and propylene.
20. The preparation method according to claim 19, characterized in that: The flow rate of the carbon source is 0.1-1 L / min.
21. A negative electrode material for a lithium battery, comprising a silicon-based negative electrode material, characterized in that: The silicon-based negative electrode material is the silicon-based composite negative electrode material according to any one of claims 1 to 5.
22. A lithium battery comprising a negative electrode and a positive electrode, characterized in that: The negative electrode is the lithium battery negative electrode material according to claim 21.
Citation Information
Patent Citations
Nano-magnesium lithium silicate / polycaprolactone composite material and preparation method thereof
CN110721336A
Method for preparing lithium magnesium silicate montmorillonite using salt lake brine water
CN1789124A